2008
DOI: 10.1016/j.neuroimage.2008.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Association between trait emotional awareness and dorsal anterior cingulate activity during emotion is arousal-dependent

Abstract: The dorsal anterior cingulate cortex (dACC) is commonly thought to subserve primarily cognitive functions, but has been strongly implicated in the allocation of attention to emotional information. In a previous positron emission tomography (PET) study, we observed that women with higher emotional awareness as measured by the Levels of Emotional Awareness Scale (LEAS) showed greater changes in regional cerebral blood flow (rCBF) in dACC induced by emotional films and recall. In the current study, we tested whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 62 publications
(77 reference statements)
10
78
0
1
Order By: Relevance
“…Furthermore, viewing of emotional pictures correlated positively with the individual TAS-20 scores but not with BDI scores in ACC. These results are in accordance with functional imaging studies demonstrating the role of the ACC in emotional processing and emotional consciousness [11,12,41] as well as with findings from lesion studies [14,15,17,18,42]. However, in contrast to Lane et al [9], we observed a stronger activation in the ACC of alexithymic subjects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, viewing of emotional pictures correlated positively with the individual TAS-20 scores but not with BDI scores in ACC. These results are in accordance with functional imaging studies demonstrating the role of the ACC in emotional processing and emotional consciousness [11,12,41] as well as with findings from lesion studies [14,15,17,18,42]. However, in contrast to Lane et al [9], we observed a stronger activation in the ACC of alexithymic subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Another model involves dysfunction of the right hemisphere evidenced by the fact that highly alexithymic individuals and patients with right hemisphere lesion show difficulties in recognizing facial expressions of emotions [2,3]. We focus on the anterior cingulate cortex (ACC) deficit model [7] since it is supported by functional imaging studies on healthy subjects [8,9,10,11] as well as by lesion studies [12,13,14,15,16] and has been in the focus of neuroimaging studies on alexithymia [4,17,18,19]. According to this model, alexithymia is associated with impoverished conscious experience of emotion caused by an altered function of the ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Lane et al [1997] have conceptualized alexithymia as a poor capacity to consciously experience emotional feelings and coined the term ''blindfeel'' (i.e., the emotional equivalent of blindsight; [Lane et al, 1997]). Furthermore, they speculated it would be associated with an abnormal participation of the ACC during emotional arousal on the basis that the level of activity in dorsal ACC to emotion-inducing stimuli was related to high-emotional awareness [Lane et al, 1998; see also McRae et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Conscious experience may also require that the information contained in stage 2 representations be made available to cognitive control structures such as dACC (Shackman et al, 2011) for use in guiding action selection. This notion of consciousness requiring that represented information be made cognitively accessible (possibly through attentional modulation; see Baars, 2002Baars, , 2005Prinz, 2012) may also explain findings relating dACC activity to differing trait levels of emotional awareness (Lane et al, 2011(Lane et al, , 1998McRae et al, 2008).…”
Section: And Prinzmentioning
confidence: 99%